Analysis of Input Tax Recalculation to Hospital Services (Case Study at PT CRB) - Putu Suari Pradnyastuti; W H Utthavi; N W D Ayuni (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
PT CRB is a taxpayer who has a business in the field of medical health services specifically eye hospital. Initially, PT CRB only reported its monthly Value Added Tax (VAT) from January to December 2019. However, the reported amount of Input Tax wasn’t in accordance. Input Taxes from drug purchases can’t be separated exactly between delivery of drugs that are VAT payable and non-VAT payable, so the Input Taxes can’t be fully credited and must be calculated with the guidelines of the Minister of Finance Regulation No. 135/PMK.11/2014. The purpose of this research was to determine the calculation of PT CRB Input Tax in 2019, the results of the recalculation of Input Taxes in accordance with PMK 135/PMK.11/2014, and the analysis of recalculated Input Taxes impact. The types of data used in this research are qualitative and quantitative data with secondary data sources. Data collection in this research is using interview techniques and documentation techniques. The data analysis technique used in this research is quantitative descriptive data analysis. Based on the results of the research, it can be concluded that the calculation of Input Tax on hospital services before recalculation shows that the total Input Tax reported by PT CRB in 2019 is about Rp. 180,518,250 and it has been fully credited. Results of the recalculation of Input Tax on hospital services at PT CRB 2019 based on PMK 135/PMK.11/2014 is Input Tax that can be credited during the January to December 2019 tax period is only Rp 63,914,935. The results of recalculated Input Taxes impact analysis are in the form of underpaid VAT of Rp 116,603,315 that be the main impact and the impact of administrative sanctions in the form of interest of 2% due to late payment of taxes.